Utilization of Audio Visual Media to Improve Student Learning Result in IPS Learning - Fauzi, Hilmi , Arif (International Journal Pedagogy of Social Studies, 2017)
This study is motivated by the low learning outcomes of students in social studies in class VII C SMP Negeri 7 Bandung. The purpose of this study is to describe the planning, implementation, results, constraints and efforts to improve student learning outcomes. This research uses PTK with Kemmis model and MC Taggart by using audio visual media in learning. The subject of this study is the students of class VII C SMP Negeri 7 Bandung as many as 40 students. Planning of this research include preparing RPP and make research instrument according to the needs of researchers. This studyÂ  was conducted for three cycles and obtained the improvement of student learning outcomes in the IPS lesson from first cycle until the third cycle. Student learning outcomes on one cycle obtained indigo with sufficient criteria, in the second cycle obtained the value with good criteria, and the third cycle obtained the value with very good criteria. The increase is one of them is marked by student learning outcomes that are above the KKM. Constraints of this research is one of the difficulty to revise the learning video that there is some negative content and adjust it with RPP. These constraints can be overcome by removing part of the negative content by editing and searching for videos from a trusted source. This research uses qualitative and quantitative data analysis.